The New Public Managementis Not That Bad After All: Evidence From Estonia, Hungary and Romania - Sorin DAN (Transylvanian Review of Administrative Sciences, 2015)
This article reviews the New Public Man-agement (NPM) literature in Central and Eastern Europe, looking particularly at reforms in Estonia, Hungary and Romania. It fnds that research that assessed changes in internal processes and ac-tivities within the public sector by far outnumber research that assessed changes in outputs and outcomes. Signifcant challenges in assessing impacts make sweeping claims about whether NPM ‘works’ diffcult to support with solid evi-dence. The paper shows that NPM policy is still considered as an option for public sector mod-ernization in Central and Eastern Europe, and suggests that a number of components of NPM, if not the model as a whole, are likely to contin-ue to exert infuence on the public sector in the future.